Analysis of Factors Affecting the Digitalisation of UMKM in Using QRIS (Study on Culinary Businesses in Bandung City) - Rahlana Shidiq Azqar; Irsyad Kamal (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
One of the factors contributing to Indonesia's low Global Digitalization Index score of 33.1 is the limited digitalization among UMKM, as reflected in the adoption of QRIS by these businesses. Although QRIS is perceived as useful, barriers such as perceived ease of use, perceived cost, and social influence from consumers and competitors significantly affect attitudes toward using and behavioural intentions to use QRIS. This study aims to analyze the factors influencing the digitalization of UMKM through QRIS by a quantitative causal approach and Partial Least Squares Structural Equation Modeling (PLS-SEM). The research utilised a purposive sampling technique, gathering data from 70 culinary business respondents in Bandung City. The findings indicate that social influence and perceived ease of use have a significant and positive influence on attitudes toward using QRIS, while perceived cost has a significant negative effect, and perceived usefulness shows no significant effect. Additionally, perceived ease of use and attitudes toward using QRIS significantly and positively influence behavioural intention to use it, whereas perceived cost, social influence, and perceived usefulness do not. Mediation analysis reveals varying effects: indirect-only mediation for perceived cost and social influence, no-effect non-mediation for perceived usefulness, and complementary mediation for perceived ease of use